THE TEX OF NELLA KHARISMA’S SONGS (A SOSIOLINGUISTIC STUDY) - Sri Hesti Heriwati (Proceeding of International Conference on Art, Language, and Culture, 2019)
Language principally functions as a medium for expressing ideas, like a singer singing songs through language. Listening to the Nela Kharisma’s  song is very interesting because it uses a lot of language switching and code mixing in its text of the song. Language, according to sociolinguistic views, contains various variations. A sociolinguist emphasizes the relationship between variations and social and situational factor. This affects the language usage of musicians who at any time incorporate linguistic elements outside the original language. In connection with the variety of language usage, someone who is called a bilingual occurs. Sociolinguistics as a linguistic branch views or places the position of language in relation to the use of language. The symptom of switching language use due to the changing situation is called code switching. A code switching talk is usually followed by code mixing, namely the existence of a base code that is used and has an autonomous function. A speaker who speaks more than one language will have the opportunity to mix code. But that does not mean that the speakers who master more languages always apply more code mixing. When a speaker slips a lot of other language into the language he is using, it is called code mixing. The background of the occurrence of the code switching and mixing can be seen from the mixing of the language of a person/character using more than one language. Special characteristics of the speakers will color the code. This paper will talk about the problem of switching from one language to another using sociolinguistic approaches and linguistic analysis methods. The result achieved is to know how far the use of language of Nela Kharisma is with the song text.